Legal Protection for Children and Women against Violence in the Perspective of Pancasila - Khansa Ananda Dewi Wahyudi; Habibah, Siti Maizul (Jurnal Perempuan dan Anak, 2023)
There's been a lot of violence against children and women lately. Starting from physical or verbal violence, resulting in many victims falling, some were injured, experienced severe trauma, and some died. The purpose of making this article is to find out what factors lead to violence against children and women, and the impact of this violence and solutions for handling this violence based on the perspective of Pancasila. Pancasila has 5 precepts, and each precept contains values that can be applied to everyday life. Violence against children is a violation of the second precept because the precepts are based on justice and accompanied by proper and polite manners in accordance with the norms in Islamic law, while violence against children and women is a violation of the second Pancasila precept because, a child and women should get compassion and justice instead of suffering and violence.